The good death an exploration of dying in America - Neumann, Ann 1968- (Beacon Press, 2016)
"Following the death of her father, journalist and hospice volunteer Ann Neumann sets out to examine what it means to die well in the United States. If a good death exists, what does it look like? This question lies at the heart of Neumann's rigorously researched and intimately told journey along the ultimate borderland of American life: American death. From church basements to hospital wards to prison cells, Neumann charts the social, political, religious, and medical landscape to explore how we die today. The Good Death weaves personal accounts with a historical exploration of the movements and developments that have changed the ways we experience death. With the diligence of a journalist and the compassion of a caregiver, Neumann provides a portrait of death in the United States that is humane, beautifully written, and essential to our greater understanding of the future of end-of-life care"...